India : a history - Keay, John. (New York: Atlantic monthly press, 2000)
The story of the Indian subcontinent, "one of the world's most fascinating and complicated regions, the home of a billion and a half people, several major religions, and one of the world's oldest and most richly diverse civilizations."--Jacket.
Includes bibliographical references (p. 545-557) and index.
Keywords: India -- History